Analisis Kinerja guru berdasarkan faktor pelatihan, kompetensi dan Karakteristik Individu pada SD Negeri Se-Kecamatan Bandar Baru Pidie Jaya - Safrida, Safrida; Kamaruddin, Kamaruddin (Aceh Cooperative Care, 2022)
ABSTRACT: This study aims to analyze the performance of public elementary school teachers in Bandar Baru District, Pidie Jaya Regency based on teacher training factors, teacher competencies and individual characteristics of teachers. This research is in the form of a survey of 123 samples of teachers using a quantitative descriptive method approach and associative analysis using a path analysis model approach. With the research results obtained; (1) there is a significant direct and indirect effect of training on teacher performance, amounting to 28.41%. (2) there is a direct and indirect effect of competence on teacher performance, which is 35.42%. (3) individual characteristic factors have a direct and indirect positive effect of 41.07% on teacher performance. And (4) simulta-neously the variables of training, competence and individual characteristics affect the performance of SD Negeri teachers, Bandar Baru District, Pidie Jaya Regency